Pengaruh Peran Kepemimpinan dalam Perubahan pada PT. Rizki Mandiri Barokah - Utami R.A Padang; Nuri Aslami (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
In a good organization is an organization that continuously experiences change is a form of effort made to manage all the consequences resulting from a change. The company or organization will not change and will not run towards the aspired, if the leaders themselves, in any part, does not change and does not grow. An organization cannot grow outside until the leaders themselves grow inside. . Leadership is a leader's process of influencing followers to interpret circumstances, choose organizational goals,organizing work and motivating followers, maintaining cooperation and teams work and organize support and cooperation with parties outside the organization. leadership roles in organizations include, setting goals, taking and make decisions, take all the risks.This study aims to determine how the role of leadership in change in PT.Rizki Mandiri Barokah. The method used is a qualitative research method with a descriptive approach. Data collection techniques with observation. The results showed that the influence of the leadership role in changes in the company PT Rizki Mandiri Barokah is very important in achieving the goals of the company, because without a good leader it is difficult for the company to achieve its goals.